Bilateral bifid mandibular canal: a case report using cone beam computed tomography - Fuentes, Ramón; Farfán, Constanza; Astete, Nicolás; Garay, I.; Dias, Fernando; Arias, Alain
The mandibular canal (MC) originates in the mandibular foramen and runs bilaterally through the mandibular ramus and body, ending in the mental foramen. One of the most common anatomical variations is bifid MC, the configurations of which have been classified into four categories and sub-categories. The prevalence of these variations depends on the imaging method used. Studies carried out in panoramic X-rays and cone beam computed tomography (CBCT) show prevalences varying between 1% and 20%. In this case report we present the finding of a bilateral bifid MC by CBCT examination; we describe its location and morphological characteristics. The variation found was a type 1 bilateral bifid MC, which consists in an accessory canal originating from a single mandibular foramen and extending to the third molar or its immediate surroundings. In this report we discuss the importance of detecting these anatomical variations, as well as their implications in clinical practice.